Origin and hydrochemical evolution of confined groundwater in Shanghai, China - Zhan, Guanghui; Li, Jingzhu; Wang, Hanmei; Wen, Xiaohua; Gu, Hua (Frontiers in Earth Science, 2023)
Confined groundwater is an indispensable resource for the urban security of Shanghai, China, where multi-layer aquifer structures and human activities create a complex groundwater environment. An understanding of the hydrochemical characteristics and evolutionary mechanisms of groundwater is necessary for its protection and effective utilization, as explored in this study. Eighty-seven groundwater samples were collected from five confined aquifers. The samples were found to have two different origins, marine–continental and continental, with notably different hydrochemical characteristics. A Cl− content of 7.5meq L−1 can be used as a demarcation index for the two origins. Groundwater of marine–continental origin is dominated by ancient seawater from which Na+ and Cl− are derived, whereas Ca2+, Mg2+, and HCO3− are derived mainly from carbonate dissolution. Groundwater of continental origin is dominated by the effects of water–rock interaction, where major ions are derived mainly from silicate weathering and carbonate dissolution. In both types of groundwater, SO42− is derived mainly from insoluble sulfides that are present in low quantities, whereas the SO42− in the few samples with high contents of insoluble sulfides is derived from human activities. Cation exchange is another controlling factor for the hydrochemical composition of groundwater, and waters of the two origins have different reaction modes: reverse cation exchange is dominant in marine–continental groundwater, whereas positive cation exchange is more common in continental groundwater. Over the past century, saline water has flowed into the groundwater funnel region nowing to human activities, resulting in changes in hydrochemical composition. The recent influx of fresh groundwater and artificial recharge has caused groundwater salinization and mineral re-dissolution.